2003
DOI: 10.1074/jbc.m302339200
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Interferes with Transforming Growth Factor-β Signaling through Direct Interaction of YB-1 with Smad3

Abstract: Transforming growth factor-␤ (TGF-␤) and interferon-␥ (IFN-␥Physical interaction between Smad3 and YB-1 was demonstrated by immunoprecipitation-Western blot analyses, and electrophoretic mobility shift assays using the recombinant Smad3 and YB-1 proteins indicated that YB-1 forms a complex with Smad3 bound to the Smadbinding element. Glutathione S-transferase pull-down assays showed that YB-1 binds to the MH1 domain of Smad3, whereas the central and carboxyl-terminal regions of YB-1 were required for its inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
149
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(162 citation statements)
references
References 50 publications
10
149
0
3
Order By: Relevance
“…In nuclear extracts prepared from hPFBs treated with TNF-␣ alone (c), binding of YB-1 repressor protein to the reverse strand of DNA encompassing the THR region of the SM␣A promoter increased by ϳ60% over baseline levels (p Ͻ 0.05). type I collagen promoter by TGF␤1 through the formation of a sequestering complex with Smad3 (Higashi et al, 2003). In addition, our previous studies on hPFBs showed that TGF␤1 displaced YB-1 from the reverse strand of THR site in the SM␣A promoter (Zhang et al, 2005).…”
Section: Binding Of Egr-1 To the Sm␣a Promoter Has Opposite Effects Omentioning
confidence: 88%
See 3 more Smart Citations
“…In nuclear extracts prepared from hPFBs treated with TNF-␣ alone (c), binding of YB-1 repressor protein to the reverse strand of DNA encompassing the THR region of the SM␣A promoter increased by ϳ60% over baseline levels (p Ͻ 0.05). type I collagen promoter by TGF␤1 through the formation of a sequestering complex with Smad3 (Higashi et al, 2003). In addition, our previous studies on hPFBs showed that TGF␤1 displaced YB-1 from the reverse strand of THR site in the SM␣A promoter (Zhang et al, 2005).…”
Section: Binding Of Egr-1 To the Sm␣a Promoter Has Opposite Effects Omentioning
confidence: 88%
“…Similarly, mononuclear cell release of IFN␥, a T-helper 1 cytokine that often functions in tandem with TNF-␣, suppresses fibroblast proliferation and collagen deposition and has long been associated with classic type I, innate-immune responses (Kunkel et al, 2003). Notably, the antifibrotic activity of IFN␥ seems to be partly based on its ability to functionally sequester TGF␤1 receptor-regulated Smad3 protein as a heteromeric complex with the YB-1 transcriptional repressor protein thus preventing binding of activated Smads to their cognate CAGA cis-activation sequence motifs in the type I collagen promoter (Higashi et al, 2003;Dooley et al, 2006). Aside from this one mechanistic detail, the molecular pathways governing termination of TGF␤1-mediated myofibroblast differentiation are not well understood but theoretically important in the search for new therapeutic targets to prevent chronic fibroproliferative diseases of the heart, lung, liver, and kidney.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, several genes important for wound healing and cellular proliferation and survival are regulated by YB-1, including collagen alpha1 and alpha2 (Norman et al 2001;Higashi et al 2003), matrix metalloproteinase 2 (Mertens et al 1997), the B-chain isoform of plateletderived growth factor (Stenina et al 2000), vascular endothelial growth factor (Coles et al 2004), granulocyte-macrophage-colony stimulating factor (Coles et al 2000), and Fas death receptor (Lasham et al 2000); moreover, YB-1 can also regulate αSMA and human pulmonary myofibroblasts (Zhang et al 2005). Takahashi et al (2010) reported that YB-1 is increased in the angiogenic endothelial cells of various tumors and is involved in the growth of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%